Radiotherapy enhances uptake and efficacy of 90Y-cetuximab: A preclinical trial. (February 2021) - Dietrich, Antje; Andreeff, Michael; Koi, Lydia; Bergmann, Ralf; Schubert, Maik; Schreiner, Lena; Löck, Steffen; Sihver, Wiebke; Freudenberg, Robert; Hering, Sandra; Pietzsch, Hans-Jürgen; Steinbach, Jörg; et al.
Highlights: Combination of molecular and external radiotherapy could enhance tumor dose and target metastases. Preclinical trial: fractionated radiotherapy in combination with 90 Y-Cetuximab. In vivo optical imaging of Cetuximab tumor uptake to optimize scheduling. The results indicate a remarkable potential to improve curative treatment outcome. Abstract: Background and purpose: Systemic molecular radiotherapy utilizes internal irradiation by radionuclide-labeled tumor-targeting agents with the potential to destroy (micro-)metastases. However, doses that are applicable in solid tumors do not reach the levels nessecary for tumor control. Thus, the combination of molecular and external radiotherapy is a promising treatment strategy, as enhanced tumor doses can be delivered with and without minor overlapping toxicities. Here, we combined a 90 Y-labeled anti-EGFR antibody (Cetuximab) with clinically relevant fractionated radiotherapy in a preclinical trial using head and neck squamous cell carcinoma xenograft tumors. Materials and methods: To model 90 Y-Cetuximab uptake for treatment schedule optimization, FaDu-bearing mice were injected with near-infrared-labeled-Cetuximab at different time points during radiotherapy with differing doses. Cetuximab uptake was longitudinally followed by in vivo-optical imaging. Tumor control probability experiments with fractionated radiotherapy (30 fx, 6 weeks, 8 dose groups/ arm) in combination with 90 Y-Cetuximab were performed to test the curative potential. Results: Imaging of near-infrared-labeled-Cetuximab uptake revealed that low to moderate external beam doses can enhance antibody uptake. Using the optimized schedule, combination of molecular and external radiotherapy using 90 Y-Cetuximab at a dose that did not result in permanent tumor inactivation in previous experiments, led to substantially increased tumor control compared to radiotherapy alone. Conclusion: Our results indicate that combination of radiolabeled therapeutics with clinically relevant fractionated radiotherapy has a remarkable potential to improve curative treatment outcome. Application of some radiation dose prior to injection may improve drug uptake and enable patient stratification and treatment personalization via a corresponding PET-tracer during therapy.